Mental retardation - Dolce, Laura (New York : Chelsea House Publishers, 1994)
An examination of mental retardation, including its history, how it occurs, and methods of education and treatment.
Includes bibliographical references (p. 101-102) and index.
Horn Book.
Wilson's Junior High School.
7-9
Young Adult
Keywords: Mental retardation -- Juvenile literature; Learning disabilities; Mentally handicapped; Learning disabilities; Mentally handicapped